2019
DOI: 10.1088/1361-6463/ab0ab7
|View full text |Cite
|
Sign up to set email alerts
|

Full-wave modelling of terahertz frequency plasmons in two-dimensional electron systems

Abstract: While models of terahertz frequency plasmons in 2D electron systems are usually developed by reducing the number of spatial dimensions, fully 3D models may be needed for the design and analysis of realistic structures. Using full-wave electromagnetic simulations, we have analysed the plasmons and magnetoplasmons observed in two recent experiments. Here, we demonstrate agreement between the theoretical and the experimental results, and discuss further device characteristics such as plasmon transmission, reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This was exactly the case in Wu et al's study as they found that the coplanar mode coupled better to their sample than the slotline mode. Follow up full wave modeling supported this experimental result, finding that decoupling the gate line from the ground plane better coupled the waveguide modes to the plasmon modes [83]. In such a way, the general electric field orientation can be controlled with careful choice of circuit design.…”
Section: Circuit Design Considerationsmentioning
confidence: 65%
“…This was exactly the case in Wu et al's study as they found that the coplanar mode coupled better to their sample than the slotline mode. Follow up full wave modeling supported this experimental result, finding that decoupling the gate line from the ground plane better coupled the waveguide modes to the plasmon modes [83]. In such a way, the general electric field orientation can be controlled with careful choice of circuit design.…”
Section: Circuit Design Considerationsmentioning
confidence: 65%
“…The resulting empirical relationship was n = 10 15 × (−0.06418V 4 g − 0.14201V 3 g − 0.16056V 2 g + 0.5462V g + 7.5), where V g is in Volts and n is in m −2 . In addition, we approximated the frequency content of the excitation pulses by assuming that the excitation amplitude decays exponentially with frequency f , as exp(−7.5f × 10 −12 ) [49]. For the rectangular device, compared to our previous experiments [33], we were able to observe more resonances, owing to shortened ungated portions of the channel that leads to smaller propagation loss.…”
Section: Methodsmentioning
confidence: 95%